Embryo Implantation In Intracytoplasmic Sperm Injection-Stimulated Cycle Using Testicular And Epididymal And Ejaculated Sperm From Azoospermic, And Severely- Teratospermic Men. - Ridha-Barzanchi, Mundhir T.; Khunda, Sarmad S.; AI-Anssari, Saeeda, A. M.; Kanan, Zuhair A.; Khunda, Sarmad S.; AI-Omari, Wafa R. S.; Al-Badri, Abedal H. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: The infertility affects about 20% to 28% of Iraqi population and the primary and secondary infertility cover 80% and 20% of infertility cases respectively. It has been shown that the major male infertility factors include oligospermia, astheno-spermia, teratospermia and azoospermia. Objectives: The objective of this study was to compare the fertilizing capacity, in vitro embryonic developmental rate and embryo implantation following the use of epididymal, testicular, and ejaculated sperm in azoospermic and severely teratospermic men. Patients and Methods: The males in experiment one were divided into three groups, severely teratospermic group (STSG, n=44), azoospermic-epididymal group (ASEG, n=35) and azoospermic-testicular group (ASTG, n=40). In experiment two the azoospermic patients were divided into two groups, obstructive (OASG, n=35) and non-obstructive (NASG, n=42). Both groups were underwent testicular extraction and intracytoplasmic sperm injection (TESE-ICSI) treatments. Results: Concentration of FSH, LH, prolactin was significantly higher in non-obstructive group compared to obstructive group (P<0.001). The concentrations of testosterone and the volume of the testes were significantly higher in the obstructive group versus non-obstructive group (P <0.01). Percentages of the fertilizable oocytes and the number of the transferred embryos per patient in the ASTG group were significantly lower compared to STSG and ASEG groups. The pregnancy and implantation rates were not significantly different in the STSG, ASSEG, and ASTG groups. ICSI rate and embryo developmental rate and the number of the transferred embryos per patient were significantly lower in the non-obstructive group (NASG) compared to the obstructive group (OASG) Pregnancy and viable fetus percentages were similar between both groups (P>0.05). Conclusions: Sources of sperm retrieval found to have no effect on embryo implantation and pregnancy rates when viable sperm are available for ICSI. Pregnancy and viable gestation sac percentages were not affected by the etiology of azoospermia in either obstructive, or nonobstructive with focal areas of spermatogenesis were present in testes of azoospermic men.